Do Markets Erode Social Responsibility? - Björn Bartling; Roberto A. Weber (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies the stability of socially responsible behavior in markets. We develop a laboratory product market in which low-cost production creates a negative externality for third parties, but where alternative production with higher costs entirely mitigates the externality. Our data reveal a robust and persistent preference for avoiding negative social impact in the market, reflected both in the composition of product types and in a price premium for socially responsible products. Socially responsible behavior in the market is generally robust to varying market characteristics, such as increased seller competition and limited consumer information. Fair behavior in the market is slightly lower than that measured in comparable individual decisions.
Keywords: C92; D03; D62; 330; social responsibility; markets; externalities; competition; fairness